Problematika Penempatan Tenaga Kerja Asing Kaitannya dengan Disharmonisasi Hubungan Kerja dan Nasionalisme Pekerja Lokal - Nugraha Pranadita; Tjutju Yuniarsih; Hady Siti Hadijah (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
Accelerating national development requires a certain amount of foreign investment. Meanwhile, the state has an obligation to protect local business actors and workers who are clearly “threatened” by the influx of foreign investment. In fact, the entry of foreign investment is often accompanied by the entry of foreign workers (TKA) as one of the conditions for the entry of the intended investment. Ideally, foreign workers who enter Indonesia have higher qualifications than domestic workers so that they can carry out the process of transferring technology and / or transferring knowledge to local workers. In fact, many foreign workers who enter Indonesia do not have adequate qualifications, causing conflicts with local workers. These conflicts generally lead to a salary or wage gap that is not accompanied by superior competence. Based on this, this research is important to do in order to better understand the dilemma of placing foreign workers from the perspective of Human Resources (HR). This research is a descriptive study which analyzed qualitatively using secondary data and primary data. The results of this study are; disharmony between foreign workers and local workers is due to the lack of training for local workers. Meanwhile, the emergence of narrow nationalism among workers is caused by a lack of understanding of different cultures and values